Training and Application of Nutritional Care Process for Nutritionist at the Puskesmas - Roziana; Aslis Wirda Hayati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Handling and implementation of good nutrition care in various conditions needs to be done in the right way and well documented, in the future every nutritionist working at the puskesmas can understand the Nutrition Care Process (NCP), able to apply it in daily work, and be handled properly and appropriately. Analysis of situation at all Puskesmas in Kampar District, not all nutritionist understand and apply the NCP method in a structured daily work. This activity aims to increase the knowledge, roles and functions of professional nutritionist in Puskesmas by implementing the NCP. The training method used focuses on discussion and discussion of case studies that occur in the field. The results of the pre and posttest showed that there was an increase in the knowledge of health center nutritionists in preparing the NCP by 52%. While the results of the paired t test showed an increase in knowledge before and after training (p-value = 0.0001). The success of understanding and implementing NCP can be influenced by several factors such as the practitioner's knowledge and skills of practitioners so that it is expected to increase the success of the puskesmas nutrition program.